Konsep Tanggung Jawab Orang Tua terhadap Anak dalam al-Qur’an (Kajian Tafsir al-Nukat wa al-‘uyun dan Tafsir al-Maraghi atas Surah Luqman Ayat 12-19) - Nofri Gunawan; Musli Musli; Mohd. Arifullah (Ar-Raniry: International Journal of Islamic Studies, 2022)
This research is actually motivated by a dichotomous view between men and women. This problem is interesting because, the Qur'an itself never mentions that the parenting and education of children is only borne by the mother. The Qur'an strongly emphasizes the concept of cooperation, or maybe the Qur'an provides an example that this is not only a mother's business as stated in Surah Luqman 12-19. The method used in this study is the muqarran method promoted by Abu Hayy al-Farmawi. In simple terms, this method works to analyze two or more interpretations of scholars who live contemporaneously or who have a very long life distance. From the discussion presented in this study, the author comes to the conclusion that: in classical commentary discourses, the style used by a commentator varies depending on the expert's knowledge of the muafssir. Among the styles that exist at this time are fiqh, linguistic, Sufism, and theological styles. While the method that is widely used by commentators at this time is the tahlili method with the source bil ma'tsur. In addition, the classical and modern interpretations related to parental responsibilities are as follows: first, according to the classical commentators, the activities of nurturing, taking care of, educating and ensuring that a child is not only borne by the mother, but also the father must make a good contribution as well. in that case. Second, not much different from the classical commentators, interpreters from the modern era also say the same thing. According to him, the job of ensuring morals and nurturing and educating children is a shared duty with both parents, not only mothers and not only fathers on the other hand. Both must work together and complement each other.